THE INFLUENCE OF POWER, WORK DESIGN AND INNOVATION ON QUALITY OF SERVICE - Mariasih, Ari (Journal of Education Research in Administration and Management (JERAM), 2017)
The objective of the research were to analyze the influence of power, work design, and innovation on the teacher quality of service in the Dinas Pendidikan Wilayah II Kota Administrasi East Jakarta. The research was conducted by teachers at SMAN (Public High School) in Kecamatan Makasar , Dinas Pendidikan Wilayah II Kota Administrasi East Jakarta. The research problems were (1) there was a direct effect of power on quality of service, (2) there was a direct effect of work design on quality of service , (3) there was a direct effect of innovation on quality of service , (4) there was a direct effect of power on innovation, (5) there was a direct effect of work design on innovation. The research implemented descriptive-correlation method and path analysis. The number of samples was 163 teachers. The result of research describe that: (1) there was a direct effect of power on quality of service, (2) there was a direct effect of work design to quality of service , (3) there was a direct effect of innovation to quality of service , (4) there was a direct effect of power on innovation, (5) there was a direct effect of work design on innovation. Moreover, finding reommended that: to increase the quality of service (1) increasing power of headmaster, (2) increasing work design of school in in Kecamatan Makasar , Dinas Pendidikan Wilayah II Kota Administrasi East Jakarta